Improving Access to Banking: Evidence from Kenya - Allen, Franklin; Carletti, Elena; Cull, Robert; Qian, Jun QJ; Senbet, Lemma; Valenzuela, Patricio (Review of Finance, 2021)
Abstract We explore the relationship between bank branch expansion, financial inclusion, and profitability for Equity Bank. Unlike traditional banks, including foreign and government owned banks in Kenya, Equity Bank targets less developed territories and less privileged households. Its presence increased financial inclusion by 31% of the adult population between 2006 and 2015, especially for Kenyans who were less educated, did not own their own home, and lived in less-developed areas. The bank’s business model proves to be highly effective, with branch-level profits rising in areas with a smaller number of operating banks. Overall, the growth of Equity Bank demonstrates that financial inclusion can be achieved and sustained through profitable branching and service strategies that also serve the needs of underserved regions and populations. Thus, financial inclusion need not come at the sacrifice of bank profitability.